2020
DOI: 10.1159/000507759
|View full text |Cite
|
Sign up to set email alerts
|

RBM5 Acts as Tumor Suppressor in Medulloblastoma through Regulating Wnt/β-Catenin Signaling

Abstract: Introduction: RBM5 acts as a tumor suppressor gene in lung and breast cancers; however, its role in the pathogenesis of medulloblastoma (MB) remains unclear. We previously identified 4 RBM5 mutations in whole exome sequencing analysis of 40 MB patients. This study examined the role of RBM5 in MB progression. Methods: The expression patterns of RBM5 in tissues of 40 MB patients were analyzed using immunohistochemistry. Associations between RBM5 expression and overall survival (OS) were evaluated using Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…RBM5 is a tumor suppressor gene in lung cancer and breast cancer, but its role in the pathogenesis of medulloblastoma (MB) remains unclear. Yu et al Found that RBM5 knockdown induced Daoy and ons-76 cells proliferation, and the b-Catenin protein expression level was up-regulated in Daoy cells, Therefore, RBM5 may regulate Wnt/b-Catenin signal transduction plays a tumor suppressive role in MB (36). Jiang et al Found similar results.…”
Section: Rbm Protein Can Inhibit Tumor Proliferation By Regulating Signal Pathwaymentioning
confidence: 88%
See 1 more Smart Citation
“…RBM5 is a tumor suppressor gene in lung cancer and breast cancer, but its role in the pathogenesis of medulloblastoma (MB) remains unclear. Yu et al Found that RBM5 knockdown induced Daoy and ons-76 cells proliferation, and the b-Catenin protein expression level was up-regulated in Daoy cells, Therefore, RBM5 may regulate Wnt/b-Catenin signal transduction plays a tumor suppressive role in MB (36). Jiang et al Found similar results.…”
Section: Rbm Protein Can Inhibit Tumor Proliferation By Regulating Signal Pathwaymentioning
confidence: 88%
“…Yu et al. Found that RBM5 knockdown induced Daoy and ons-76 cells proliferation, and the β-Catenin protein expression level was up-regulated in Daoy cells, Therefore, RBM5 may regulate Wnt/β- Catenin signal transduction plays a tumor suppressive role in MB ( 36 ). Jiang et al.…”
Section: Rbm Proteins Family Is Frequently Related To the Occurrence Of Cancermentioning
confidence: 99%
“…In addition, it has been demonstrated that RBM5 acts as tumor suppressor in different cancers. Compared with normal tissues, RBM5 was significantly lower in medulloblastoma and RBM5 overexpression repressed cell proliferation and migration in vitro [ 35 ]. Zilun et al demonstrated that long noncoding RNA LINP1 (LncRNA LINP1) inhibited apoptosis and promoted proliferation by repressing RBM5 in gastric cancer cells, suggesting that RBM5 plays a tumor suppressor role in gastric cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…All plasmids were then transformed into chemically competent E.coli BL21 (DE3) cells for expression. To produce unlabeled, 15 N-or 13 C- 15 N uniformly labeled protein samples, the cells were grown either in Luria-Bertani (LB) or M9 minimal media supplemented with 15 NH4Cl/ 13 C-glucose and 50 g/ml Kanamycin. For constructs containing the zinc finger (ZnF1) domain, the cultures were supplemented with 100 ZnCl2solution for proper folding of the domain.…”
Section: Protein Expression and Preparationmentioning
confidence: 99%
“…RNA-binding motif protein 5 (RBM5, also known as H37 or LUCA-15) is a trans -acting RNA binding protein, which is down-regulated in a variety of cancers including primary lung 8 , prostate 9 , certain breast cancers 10 and vestibular schwannomas 11 . It has also been suggested to regulate metastasis by directly altering expression and activation of proteins important for this process, including Rac1 and β-catenin 12,13 . RBM5 belongs to a larger protein family that includes the related RNA binding proteins RBM6 and RBM10, which share a similar domain organization and exhibit high sequence similarity with RBM5 (30% and 50%, respectively) ( Fig.…”
Section: Introductionmentioning
confidence: 99%